Comparative plastome evaluation, phylogenomic analysis, and DNA signatures of medicinally important malvaceous genera and their adulterants - Satish Maurya; Geetika Sukhramani; Changyoung Lee; Sangjin Jo; Jinki Kim; Eun Ju Jeong; Nelson A. Zamora; Randall Garcia; Zhiyun Zhang; Sangho Choi; Ritesh Kumar Choudhary; Soo-Yong Kim (Scientific Reports)
Abstract The Bala group of plants, classified under the Malvaceae family, is acknowledged in the Ayurvedic Pharmacopoeia of India and is well-known for its medicinal uses, especially in boosting vitality and addressing neurological and cardiovascular conditions. The key genera of this group, such as Sida and Abutilon, are highly valued in traditional medicine; however, the efficacy of herbal formulations is frequently compromised by adulterants from morphologically similar genera like Malvastrum and Malva. To address this critical challenge, our study focuses on plastome sequencing of various Bala group taxa and their adulterants, aiming to delineate DNA signatures for key species and provide a robust strategy against adulteration. Comprehensive analyses of plastomes from Sida, Abutilon, Malvastrum, and Malva reveal distinct indels, simple sequence repeats (SSRs), and tandem repeats across coding and non-coding regions, as well as potential DNA barcodes within specific intergenic regions. Investigations into gene composition, genetic variations, and nucleotide diversity further elucidate phylogenetic relationships within the Malveae tribe. Phylogenomic analyses clarify the placement of the Bala group and its adulterants, offering robust insights into their evolutionary context. This study underscores the utility of plastome-based approaches in safeguarding the authenticity of Bala group herbal drugs and highlights the broader implications for quality assurance in traditional medicine.